MicroRNA-499 expression distinctively correlates to target genes sox6 and rod1 profiles to resolve the skeletal muscle phenotype in nile tilapia - Nachtigall, Pedro G. [UNESP]; Dias, Marcos C. [UNESP]; Carvalho, Robson F. [UNESP]; Martins, Cesar [UNESP]; Pinhal, Danillo [UNESP] (Public Library Science, 2015)
A class of small non-coding RNAs, the microRNAs (miRNAs), has been shown to be essential for the regulation of specific cell pathways, including skeletal muscle development, maintenance and homeostasis in vertebrates. However, the relative contribution of miRNAs for determining the red and white muscle cell phenotypes is far from being fully comprehended. To better characterize the role of miRNA in skeletal muscle cell biology, we investigated muscle-specific miRNA (myomiR) signatures in Nile tilapia fish. Quantitative (RT-PCR) and spatial (FISH) expression analyses revealed a highly differential expression (forty-four-fold) of miR-499 in red skeletal muscle compared to white skeletal muscle, whereas the remaining known myomiRs were equally expressed in both muscle cell types. Detailed examination of the miR-499 targets through bioinformatics led us to the sox6 and rod1 genes, which had low expression in red muscle cells according to RT-qPCR, FISH, and protein immunofluorescence profiling experiments. Interestingly, we verified that the high expression of miR-499 perfectly correlates with a low expression of sox6 and rod1 target genes, as verified by a distinctive predominance of mRNA destabilization and protein translational decay to these genes, respectively. Through a genome-wide comparative analysis of SOX6 and ROD1 protein domains and through an in silico gene regulatory network, we also demonstrate that both proteins are essentially similar in vertebrate genomes, suggesting their gene regulatory network may also be widely conserved. Overall, our data shed light on the potential regulation of targets by miR-499 associated with the slow-twitch muscle fiber type phenotype. Additionally the results provide novel insights into the evolutionary dynamics of miRNA and target genes enrolled in a putative constrained molecular pathway in the skeletal muscle cells of vertebrates.